Особливості використання спеціальних знань під час розслідування вбивств, учинених засудженими в місцях позбавлення волі - Кікінчук, В. В.; Kikinchuk, V. V.; ORCID: http://orcid.org/0000-0003-2241-6384; Мішина, К. Г.; Mishyna, K. H.; ORCID: http://orcid.org/0000-0002-7101-3787 (Право і безпека. – 2022. – № 1 (84). – С. 47-55, 2022)
Важливим фактором успішного розслідування кримінальних правопорушень є використання новітніх досягнень у сфері науки і техніки під час проведення слідчих (розшукових) дій. У наш час злочинці під час вчинення кримінальних правопорушень користуються новітніми досягненнями природних і технічних наук, а їхні дії та способи приховування злочинів стають все більш винахідливими. Для правоохоронної діяльності необхідні різноманітні знання для того, щоб їх повноцінно й ефективно використовувати для розслідування злочинів, а в подальшому і для здійснення правосуддя. У статті з урахуванням слідчої практики та аналізу теорії розкрито сутність, зміст і особливості використання спеціальних знань під час розслідування вбивств, учинених засудженими в місцях позбавлення волі.

Negative trends in the economy and social relations are slowing down the process of reforming the economic and financial system. The sharp restriction of state control and other negative phenomena that existed in our country have caused a significant increase in crime, especially its organized forms, resulting in a sharp increase in the number of particularly serious crimes against the person. A felony such as murder committed by a convict in prison is no exception. These criminal offenses invariably cause a significant public response, because, firstly, a serious criminal offense is committed, such as murder, secondly, it is committed by convicts serving sentences, and thirdly, as a rule, this category of criminal offenses is committed in correctional facilities. Convicts are persons with criminal experience who know the peculiarities of law enforcement agencies and have techniques for counteracting the investigation of criminal offenses, so the investigator faces the difficult task of identifying and exposing both the direct perpetrators and organizers (intermediaries) of such murders. That is why it is impossible to search for, record, seize and investigate the criminologically significant information about crimes of this kind necessary for the investigation and the court without the use of various special knowledge. In addition, the continuous improvement of technical means and methods significantly expands the range of specialized knowledge, which, in turn, allows you to identify, record and remove traces that were previously unavailable for research. However, the problem is that investigators are often not fully informed about the possibilities of using expertise in the investigation of criminal offenses. It should also be borne in mind that murder of this category is committed in a specific situation, namely in correctional facilities. All the above determined the relevance of the chosen research topic.

Важным фактором успешного расследования уголовных правонарушений является использование новейших достижений в области науки и техники при проведении следственных (розыскных) действий. В настоящее время преступники при совершении уголовных правонарушений пользуютс я новейшими достижениями естественных и технических наук, их действия и способы сокрытия преступлений становятся все более изобретательными. Для правоохранительной деятельности необходимы разнообразные знания, чтобы их полноценно и эффективно использовать в расследовании преступлений, а в дальнейшем и совершении правосудия. В нашей статье раскрыты сущность, содержание и особенности использования специальных знаний при расследовании убийств, совершенных осужденными в местах лишения свободы.
Features of the special knowledge use in the investigation of murders committed by convicts in prisons
Особенности использования специальных знаний при расследовании убийств, совершенных осужденными в местах лишения свободы
Кікінчук, В. В. Особливості використання спеціальних знань під час розслідування вбивств, учинених засудженими в місцях позбавлення волі / Василій Васильович Кікінчук, Карина Григорівна Мішина // Право і безпека. – 2022. – № 1 (84). – С. 47-55. – DOI: https://doi.org/10.32631/pb.2022.1.05.
Кікінчук, В. В. і Мішина, К. Г. (2022) «Особливості використання спеціальних знань під час розслідування вбивств, учинених засудженими в місцях позбавлення волі», Право і безпека, 84(1), с. 47-55. doi: 10.32631/pb.2022.1.05.
Кікінчук В. В., Мішина К. Г. Особливості використання спеціальних знань під час розслідування вбивств, учинених засудженими в місцях позбавлення волі. Право і безпека . 2022. No 1 (84). С. 47 –55. DOI: https ://doi.o rg/10.32631/pb.20 2 2. 1 .05.
Kikinchuk, V. V., and Mishyna, K. H. (2022). Features of the special knowledge use in the investigation of murders committed by convicts in prisons . Law and Safety, 1 (84), 47– 55 . https ://doi.o rg/10.32631/pb.20 22. 1 .05 .
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; спеціальні знання; судова експертиза; вбивство; місця позбавлення волі; special knowledge; forensic examination; murder; places of imprisonment; criminal offense; специальные знания; судебная экспертиза; убийство; места лишения свободы; уголовное преступление